Nickel increases productivity, Ca accumulation and reduces blossom-end rot in tomato - Macedo, Fernando Giovannetti [UNESP]; De Melo, Wanderley José [UNESP]; Delarica, Denise De Lima [UNESP]; Cruz, Renata Beatriz; Santos, Elcio Ferreira; De Melo, Gabriel Maurício Peruca; Mattiuz, Ben Hur [UNESP]; Cruz, Mara Cristina Pessôa da [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP] (Taylor & Francis, 2021)
Blossom-end rot (BER) is a physiological disorder related to calcium (Ca) deficiency in tomato fruits. However, adequate Ca supply is not sufficient to inhibit the BER incidence. The Ni-Ca interaction has increased the Ca content in Ni hyperaccumulators plants. However, studies with commercial plants are still incipient. The objective of this work was to evaluate the effect of Ni-Ca interaction in tomato plants, focusing on yield and incidence of BER. We carried out two trials. The first trial two Ca doses was used: sufficient Ca 0.70 g kg−1 (Ca S) and deficient Ca 0,35 g kg−1 (Ca D) and; four Ni doses applied via substrate (0.0; 0.5; 1.0 and; 2.0 mg kg−1). In the second trial, the same Ca doses of the first trial and four doses of Ni (0.0; 0.08; 0.42 and; 0.84 mM) applied, via foliar, at the beginning of flowering were used. We verified that the Ni-Ca interaction increased the tomato fruits yield, the shoot calcium accumulation reduced the BER incidence and increased the time of fruit color change (green to red). Even under stressed conditions such as a low Ca availability. Both Ni application ways showed positive results for fruit yield and decreased BER incidence.
Keywords: Crop production; horticulture; micronutrient; nutrient interaction; physiological disorder; plant nutrition